Keterampilan Menulis Dan Bercerita Untuk Membangkitkan Kecintaan Sejarah Bagi Generasi Muda - Murdiyah Winarti; Ayi Budi Santosa; Iing Yulianti; Faujian Esa Gumelar; Nurdiani Fathiarini (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
This research aimed to develop a Community Service Program that focuses on improving the reading and writing skills of elementary and junior high school youth regarding local history in the East Bandung area. The program addressed issues such as the need for more understanding of local history, low interest in historical topics, and limited writing and storytelling skills among adolescents in the area. The program began with delivering material on writing and storytelling skills and local historical concepts to the participants. Although initially hesitant and embarrassed, the participants gradually became enthusiastic about sharing their stories. The program then continued with the practice of historical storytelling through objects in East Bandung, starting with the Bandros bus tour. The young educators within Bandros supported the program by hosting visits to Teras Sunda and Tugu Perjuangan. The program laid the foundation for habitual action to write and tell stories about local history among teenagers. The participants demonstrated their ability to tell stories with simple narrative formulations, such as what, where, when, who, why, and how. However, the program faced challenges in terms of timeliness, and the young participants were still hesitant to write down ideas related to historical places in their surroundings. Overall, the Community Service Program can potentially improve historical awareness and writing skills among the millennial generation in the East Bandung area.Keywords: Historical awareness, writing skills, millennial generation.